"Migration with Dignity": Towards a New Zealand Response to Climate Change Displacement in the Pacific - Farquhar, Harriet (Victoria University of Wellington Law Review, 2015)
The impacts of climate change threaten to cause the displacement of millions of people worldwide by the middle of this century. Despite this looming crisis, international law provides insufficient protection to those who will be forced to migrate. In most cases, those who are displaced will fall outside of current protection frameworks. This article examines why this protection deficit should be of particular concern to New Zealand, and argues that there are significant incentives for New Zealand to develop a response to the issue of climate change displacement in the Pacific. The article concludes that in order to ensure Pacific peoples are able to migrate with dignity, migration schemes which are pre-emptive and voluntary should be put in place to facilitate migration flows. These should build upon New Zealand’s current immigration framework, and include the extension of current permanent and temporary migration schemes, as well as the introduction of labour-training migration schemes.